Papers on the cultivation of cotton in India (Harrison, 1840)
Contains : On the introduction of Pernambuco cotton on the western side of India / by Charles Lush. Report of the Cotton Committee of the Agricultural and Horticultural Society of India / chairman F.C. Smith.